Epidemiological profile of pneumonia associated with mechanical ventilation in the pre- and trans-pandemic period of COVID-19 in a hospital in southern Brazil (Research, Society and Development, 2025)
Ventilator-associated pneumonia (VAP) is a common infection in ICUs, occurring after 48 hours of mechanical ventilation and diagnosed based on clinical, radiological, and laboratory criteria. This study analyzed the medical records of 190 adult patients diagnosed with VAP at Hospital Nossa Senhora da Conceição (HNSC) in Tubarão, SC, aiming to assess the epidemiological profile in the pre- and trans-pandemic periods of COVID-19, between 2018 and 2020. The results indicated an increase in the rate of mechanical ventilation use, along with a significant rise in VAP density in 2020, suggesting a direct impact of the pandemic on case incidence. Epidemiological analysis can contribute to the implementation of more effective preventive strategies and the reduction of adverse outcomes.